Sisters in resistance : how a German spy, a banker's wife, and Mussolini's daughter outwitted the Nazis - Mazzeo, Tilar J. (Grand Central Publishing, 2022)
"In 1944, the war had reached its climax in continental Europe. News of secret diaries kept by Italy's former Foreign Minister, Galeazzo Ciano, had permeated public consciousness. What wasn't reported, however, was how three women-a Fascist's daughter, a German spy, and an American socialite-risked their lives to ensure the diaries would reach the Allied forces, who would use the papers as key evidence against the Nazis at the Nuremberg Trials. Just a year earlier, Edda Mussolini, Benito Mussolini's daughter, had given Hitler and her father an ultimatum: release her husband, Galeazzo Ciano, from prison, or risk her leaking her husband's journals to the press. Knowing the diaries will expose Nazi lies and create a foundation for a criminal war crimes prosecution, Hitler and Mussolini vow to do everything in their power to see the diaries destroyed-even if it means liquidating Mussolini's daughter. To do this, they ordered Hilde Beetz, a German spy, to seduce Ciano in prison in order to learn the diaries' location. As the seducer becomes the seduced, however, Hilde shifts her loyalties and becomes a double agent, joining forces with Edda to save Ciano from execution. When this fails, Edda flees to Switzerland with Hilde's daring assistance to keep Ciano's final wish: to see the diaries published for use by the Allies. When the head of United States' intelligence, Alan Dulles, learns of Edda's escape, he sends in socialite Frances De Chollet, an "accidental" spy, assigned by chance to a mission that would change her life. Her task is to find Edda, gain her trust, and, crucially, hand the diaries over to the Americans. Against all expectations, what develops is a rich and humanizing friendship between the two women. One step ahead of the Gestapo agents who are hunting Edda, together they succeed in preserving one of the most important historic documents of the Second World War. Drawing from in-depth research and first-person interviews with people who witnessed parts of this true story, Mazzeo gives readers a riveting look into this little-known moment in cultural history and shows how, without Edda, Hilde, and Frances's involvement, certain convictions would never have been possible at Nuremberg. Sisters in Resistance is a powerful look at women's intelligence work during WWII, a moving story of unlikely wartime friendships, and an inspirational investigation into three people who, navigated the place where truth, loyalty, justice, and betrayal collide"--